Topic Based Lessons for Basic Acts of Speaking in a Primary School Program (2021)
ABSTRACT: After having all the results obtained from the action research aimed at the activities that primary school programs at a public school and the students ́ reaction to the different topic-based activities brought to the classroom, a few questions about the development of the Foreign Language as an important syllabus component can still be asked. This experience was carried out in 5th and 4th grade classes through virtual interactive activities, from march to june, and face to face in a 4th grade class. All this work is the result of several class observations, interviews with teachers and school managers and the most previous interactions with the students. Such findings were the fundamentals of the actions implemented.